Peran Kepala Desa dalam Mewujudkan Pembangunan Desa yang Berkelanjutan: Sebuah Studi Literatur Kasus-kasus di Indonesia - Rinto Z.W. Abidjulu; Feliks Arfid Guampe; Join Hengkeng (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The purpose of this study is to analyze the important role of village heads in achieving sustainable village development in Indonesia. The study employs a qualitative research approach, utilizing a literature review method to explore and synthesize various studies, articles, journals, and reports related to the village heads' roles. The data collection was conducted through a systematic literature search using relevant keywords such as